Countercyclical capital requirement reductions, state dependence and macroeconomic outcomes - Elif C. Arbatli-Saxegaard; Ragnar Enger Juelsrud (Norges Bank, 2020)
We use bank-, loan- and firm-level data together with a quasi-natural experiment to estimate the impact of capital requirement reductions on bank lending and real economic outcomes. We find that capital requirement reductions increase lending both to households and firms at the bank- and loan-level, and that the increased lending to firms translates into higher capital investment at the firm-level. Furthermore, the transmission of lower capital requirements to the real economy has a "double state-dependence". The first state-dependence relates to the characteristics of banks. Specifically, the transmission of lower capital requirements to lending is stronger for banks with lower capital ratios. We interpret this result as capital requirement reductions having a larger effect when they are more binding. The second state-dependence relates to the characteristics of the corporate sector. Specifically, the transmission of lower capital requirements to real economic outcomes - via bank lending - is weaker for firms with higher default risk or more leverage, suggesting that capital requirement reductions is most effective in terms of boosting real economic outcomes when firms are financially sound.
hdl:11250/2684425
Keywords: E51; G21; G28; 330; Banking; capital requirements; macroprudential regulation